Assessing Knowledge, Attitudes, And Practices Regarding Antibiotic Use And Resistance: A Comprehensive Study Among Private Primary Care Providers And The Public In Northern Malaysia - Sathasivan, Deebadarishani (2024)
Antimicrobial resistance (amr) is considered a global health threat by the who, and unfortunately malaysia, like every other country in the world, is not immune to this danger. Studies have shown that antibiotic prescribing among primary care in malaysia is much higher in private clinics than in public clinics, and that knowledge of antibiotics among general practitioners is only moderate. This is of particular concern as the inappropriate use of antibiotics leads to antibiotic resistance in humans and subsequently has been shown to be fatal. Primary health care providers are responsible for prescribing and dispensing antibiotics to patients for various health indications. Therefore, they play an important role in ensuring the correct use of antibiotics among the public, parallel with government efforts to prevent amr. This study was conducted to fill the gaps of knowledge, attitudes and practices among healthcare providers in the private sector and the public. A cross-sectional survey using self-completed questionnaires was conducted among three different study populations of general practitioners, pharmacists and the general public in the northern states of malaysia, including perlis, kedah, pulau pinang and perak. This descriptive research was conducted during the new norm of the covid-19 pandemic.